Pendidikan Kesehatan Tentang Pemenuhan Gizi Seimbang Pada Bayi Dan Balita di Desa Joring Lombang Kecamatan Padangsidimpuan Angkola Julu Kota Padangsidimpuan: Pendidikan Kesehatan Tentang Pemenuhan Gizi Seimbang Pada Bayi Dan Balita di Desa Joring Lombang Kecamatan Padangsidimpuan Angkola Julu Kota Padangsidimpuan - Dewi, Sri Sartika Sari; Ramadhini, Delfi (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2021)
Good nutritional status of toddlers plays an important role in growth and development, especially during the golden period in the first five years. The results of the 2017 Nutritional Status Monitoring (PSG) in Indonesia showed the prevalence of stunting for toddlers was 27.5%, underweight toddlers 8.0%, very thin toddlers 3.1%, underweight toddlers 22.8%, and underweight toddlers as much as 17.8%. The purpose of this activity is to increase the knowledge of mothers on the nutritional status of toddlers so that they can reduce the incidence of malnutrition or malnutrition. This service activity was carried out simultaneously with the Posyandu for toddlers in Joring Lombang Village by weighing toddlers, providing counseling to parents/caregivers of toddlers, and providing additional food. This community service activity was attended by 32 toddlers. The results showed that the number of children under five with good nutritional status was 22 children (68.8%), undernutrition 5 children (15.6%), over nutrition 4 children (12.5%) and poor nutrition 1 child (3.1%). . Through education about balanced nutrition, there has been an increase in mother's knowledge about balanced nutrition in toddlers. Increased knowledge about balanced nutrition and food processing may be followed by behavioral changes. Nutrition counseling with the lecture method accompanied by posters and leaflets is one of the learning approaches by providing a set of knowledge and skills needed to be able to determine the right behavior choices to improve the nutritional status of their toddlers.